Policy Tools for Preventing and Handling Sexual Violence at Universitas Negeri Padang - Rico Saputra (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This research discusses the policy tools made by Padang State University (UNP) in handling cases of sexual violence within the institution. Usually when sexual violence occurs, both against lecturers and students or female students, victims are confused about where to report it. If reported to the department or faculty level, victims usually cannot be handled properly because there are no guidelines that become benchmarks in preventing and handling sexual violence on campus. Therefore, a comprehensive and integrated policy tool is needed, starting from clear reporting procedures, structured case handling mechanisms, to an adequate victim assistance system.This research is a type of descriptive research with qualitative methods. The data collection techniques used are interviews and documentation. Informants in this study include the UNP PPKS Task Force, UNP Tendik, UNP Lecturers and UNP Students. This research uses the Policy Instrument Theory from Howlett and Ramesh (1995) which divides instruments into 3 (three) groups, namely, Compulsory Policy Instruments, Voluntary Policy Instruments, and Mixed Policy Instruments.The results of this study indicate that the implementation of the policy tools of Permendikbudristek No. 30 of 2021 at UNP has been running through various policy instruments, although there are several instruments that have not been implemented optimally. Referring to the Policy Instrument Theory proposed by Howlett and Ramesh (1995) shows that of the six existing policy instruments, four instruments have been fulfilled well, namely regulations, direct provisions, voluntary organizations, and information and exhortation. The other two instruments, namely public enterprises and subsidies, have not been fulfilled optimally due to constraints in coordination with government agencies and limited funding systems. UNP needs to strengthen coordination mechanisms with government agencies and develop a direct subsidy scheme for victims of sexual violence to ensure more effective policy implementation.